A review of select minerals influencing the haematopoietic process. Issue 2 (9th July 2018) - Oliveira, Dalila Cunha; Nogueira-Pedro, Amanda; Santos, Ed Wilson; Hastreiter, Araceli; Silva, Graziela Batista; Borelli, Primavera; Fock, Ricardo Ambrósio
Abstract: Micronutrients are indispensable for adequate metabolism, such as biochemical function and cell production. The production of blood cells is named haematopoiesis and this process is highly consuming due to the rapid turnover of the haematopoietic system and consequent demand for nutrients. It is well established that micronutrients are relevant to blood cell production, although some of the mechanisms of how micronutrients modulate haematopoiesis remain unknown. The aim of the present review is to summarise the effect of Fe, Mn, Ca, Mg, Na, K, Co, iodine, P, Se, Cu, Li and Zn on haematopoiesis. This review deals specifically with the physiological requirements of selected micronutrients to haematopoiesis, showing various studies related to the physiological requirements, deficiency or excess of these minerals on haematopoiesis. The literature selected includes studies in animal models and human subjects. In circumstances where these minerals have not been studied for a given condition, no information was used. All the selected minerals have an important role in haematopoiesis by influencing the quality and quantity of blood cell production. In addition, it is highly recommended that the established nutrition recommendations for these minerals be followed, because cases of excess or deficient mineral intake can affect the haematopoiesis process.